2022
DOI: 10.1021/acs.macromol.2c00406
|View full text |Cite
|
Sign up to set email alerts
|

Interrogating the Effect of Block Sequence on Cocrystallization, Microphase Separation, and Charge Transport in All-Conjugated Triblock Copolymers

Abstract: Despite impressive progress in the research of all-conjugated diblock copolymers, there is a quite limited investigation into triblock counterparts. Moreover, regarding the block sequence, which is peculiar to triblock copolymers, its effect on their crystallization and microphase separation is still poorly understood. Herein, we design and synthesize a family of all-conjugated triblock copolymers comprising poly­(3-butylthiophene) (P3BT), poly­(3-hexylselenophene) (P3HS), and poly­(3-dodecylthiophene) (P3DDT)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 58 publications
1
7
0
Order By: Relevance
“…The block sequence is a particular parameter peculiar to triblock copolymers compared with diblock copolymers. ,, Finally, the influence of block sequence was studied by designing series C (P3OT- b -P3BT- b -P3EHT and P3BT- b -P3OT- b -P3EHT) around the block ratio of 1:1:1. Both P3OT- b -P3BT- b -P3EHT and P3BT- b -P3OT- b -P3EHT showed only one (100) peak at q z of 3.78 ( d 100 = 1.66 nm) and 3.85 nm –1 ( d 100 = 1.63 nm), respectively, indicating the formation of cocrystallization in their as-cast state (Figure a,b).…”
Section: Resultssupporting
confidence: 76%
“…The block sequence is a particular parameter peculiar to triblock copolymers compared with diblock copolymers. ,, Finally, the influence of block sequence was studied by designing series C (P3OT- b -P3BT- b -P3EHT and P3BT- b -P3OT- b -P3EHT) around the block ratio of 1:1:1. Both P3OT- b -P3BT- b -P3EHT and P3BT- b -P3OT- b -P3EHT showed only one (100) peak at q z of 3.78 ( d 100 = 1.66 nm) and 3.85 nm –1 ( d 100 = 1.63 nm), respectively, indicating the formation of cocrystallization in their as-cast state (Figure a,b).…”
Section: Resultssupporting
confidence: 76%
“…It should be pointed out that no such variation was observed in the 2-D GIXRD images of the samples of l -T-OPE 4 -DPP-OPE 4 under similar conditions (Figure S11). Previous results showed that the H-aggregate packing mode of π-conjugated segments would lead to a more pronounced crowding effect of their alkyl side chains and results in a larger d -spacing of alkyl side chains. , On the basis of these results, it was supposed that the d -spacing of about 1.85 and 1.46 nm was assigned to the domains of a crystalline π-conjugated backbone along with ordered packing alkyl side chains of l -T-OPE 4 -DPP-OPE 4 units adopted H- and J-aggregate packing modes, respectively (Figure E), and numerous l -T-OPE 4 -DPP-OPE 4 units of l -T-OPE 4 -DPP-OPE 4 - b -P2VP 44 transferred from the H-aggregate packing mode to a more slipping J-aggregate mode after the aging, leading to the decrease of d -spacing from 1.85 to 1.46 nm.…”
Section: Results and Discussionmentioning
confidence: 81%
“…), which can be readily extended to conjugated rod–rod BCPs. Recently, the co-crystallization of two conjugated blocks is found to enhance the charge transport of conjugated rod–rod BCPs. Nonetheless, the scrutiny of co-crystallization in the literature has been comparatively few owing to the difficulty in achieving conjugated polymer co-crystals. More importantly, the co-crystallization kinetics in conjugated rod–rod BCPs has been rarely explored. Clearly, the ability to process conjugated rod–rod BCPs for accessing co-crystallization and subsequently reveal the influence of processing strategies on the two competing phase behaviors (co-crystallization versus microphase separation) represents a significant endeavor toward not only providing fundamental insight into their phase behaviors but also capitalizing on the conjugated polymer co-crystals for high-performance optoelectronics.…”
Section: Introductionmentioning
confidence: 99%